Answer:
Hence The composition
of the given function is
.
Explanation:
Given:
![f(x) = x^2+2x-6](https://img.qammunity.org/2021/formulas/mathematics/high-school/568a7ul5tmhigo7g1pnvaxusdx7i141npt.png)
![g(x)=x+5](https://img.qammunity.org/2021/formulas/mathematics/high-school/pqlnhgnutxghfj8maegim1ik73srfppq5o.png)
We need to find
.
Solution:
Now we can say that;
=
![f(g(x))](https://img.qammunity.org/2021/formulas/mathematics/high-school/12kjforamp68hgqvc5txc8utt3pjqzwjh6.png)
![(fog)(x) = (x+5)^2+2(x+5)-6](https://img.qammunity.org/2021/formulas/mathematics/high-school/438nru71tkbdl4tvxqcuyt8il0me0bydr5.png)
Now Applying distributive property we get;
![(fog)(x) = (x+5)^2+2* x+2*5-6\\\\(fog)(x) = (x+5)^2+2x+10-6\\\\(fog)(x) = (x+5)^2+2x+4](https://img.qammunity.org/2021/formulas/mathematics/high-school/got5791iglg1qvlsmkt01c96u2396dd25d.png)
Now Solving the exponent function we get;
![(fog)(x) = x^2+2* x* 5+5^2+2x+4\\\\(fog)(x) = x^2+10x+25+2x+4\\\\(fog)(x) = x^2+12x+29](https://img.qammunity.org/2021/formulas/mathematics/high-school/65963e5ywecdexiu731petpf6mfgqkelp5.png)
Hence The composition
of the given function is
.